Molecular evidence provides new insights into the evolutionary origin of an ancient traditional Chinese medicine, the domesticated “Baizhi” - Lin, Yingyu; Yao, Gang; Huang, Chunxiu; Chao, Zhi; Tian, Enwei (Frontiers in Plant Science, 2024)
Baizhi" is a famous herbal medicine in China, and it includes four landraces named as 'Hangbaizhi', 'Chuanbaizhi', 'Qibaizhi' and 'Yubaizhi'. Long-term artificial selection had caused serious degradation of these germplasms. Determining the wild progenitor of the landraces would be benefit for their breed improvements. Previous studies have suggested Angelica dahurica var. dahurica, A. dahurica var. formosana or A. porphyrocaulis as potential candidates, but the conclusion remains uncertain., and their phylogenetic relationships are still in controversy. In this study, the genetic variation and phylogenetic analyses of these species and four landraces were conducted on the basis of both the nrITS and plastome dataset. Genetic variation analysis showed that all 8 population of four landraces shared only one ITS haplotype, meanwhile extremely low variation occurred within 6 population at plastid genome level. Both datasets supported the four landraces might be originated from a single wild germplasm. Phylogenetic analyses with both datasets revealed largely consistent topology using Bayesian inference and Maximum likelihood methods.Samples of the four landraces and all wild A. dahurica var. dahurica formed a highly supported monophyletic clade, and then sister to the monophyly clade comprised by samples of A. porphyrocaulis, while four landraces were clustered into one clade, which further clustered with a mixed branches of A. porphyrocaulis and A. dahurica var. dahurica to form sister branches for plastid genomes. Furthermore, the monophyletic A. dahurica var.formosana was far distant from the A. dahurica var. dahurica-"Baizhi" clade in Angelica phylogeny. Such inferences was also supported by the evolutionary patterns of nrITS haplotype network and K2P genetic distances. The outcomes indicated A. dahurica var.dahurica is most likely the original plant of "Baizhi". Considering of phylogenetic inference and evolutionary history, the species-level status of A. dahurica var. formosana should be accepted, and the taxonomic level and phylgenetic position of A. porphyrocaulis should be further confirmed. This study preliminarily determined the wild progenitor of "Baizhi" and clarified the phylogenetic relationships among A. dahurica var. dahurica, A. dahurica var. formosana and A. porphyrocaulis, which will provide scientific guidance for wild resources protections and improvement of "Baizhi".